تطوير الـمواد التعليمية لمهارة القراءة على أساس أسلوب العصف الذهن - Amrini Shofiyani (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2017)
Brainstorming model or strategy has many values, one of them : easy to apply, efficient to use, possible to be equipped with amusements and games, developing useful way of thingking creatively raising self-confidence, encouraging to express ideas freely, raising creative ideas to solve problems, concerning students' awareness and transforming the interest to think. This study aims to : 1) know the process of subjects development in reading with brainstorming model to raise the ability of Arabic text reading. 2) know how effective so far the use of subject matter of reading with brainstorming model to develop the ability Arabic text.